Polymer data handbook - Mark, James E. (Oxford University Press, 1999)
Polymers are the compounds that includes platics, artificial fibers, rubber, cellulose, and many other materials, including coatings and adhesives. This book presents key data on approximately 200 important polymers currently in industrial use or under study in industrial or academic research. No other single source covers so many polymers or offers such a depth of data. The book standardizes and makes accessible a wealth of essential data for students, teachers, researchers, and other professionals in chemistry and chemical engineering